Penguatan Kapasitas UMKM Desa melalui Pengelolaan Keuangan dan Sertifikasi Halal - Nur'aeni Nur'aeni; Mimin Mintarsih; Farhan Fakhruddinsyah (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
Sugihmukti Village, Pasirjambu District, has a growing MSME potential, especially in the food and beverage sector as well as processed businesses based on local agricultural products, which are a characteristic of the rural economy in the area. However, the existing potential has not been fully supported by adequate business management capabilities, so most MSMEs are still operating conventionally and have not focused on long-term business sustainability. In addition, many MSME actors still have limited knowledge regarding the urgency of halal certification, the stages of the application process, and the economic benefits that can be obtained from owning a halal certificate. This activity is part of community service-based research with an ABCD (Asset-Based Community Development) approach. The results of this activity show that it has been carried out successfully as part of efforts to empower village MSMEs through improved financial literacy and strengthening understanding of the importance of halal certification for businesses. The implementation of an educational approach accompanied by participatory assistance allows this activity to address the real needs of MSME actors in managing business finances in a more organized, planned, and systematic manner.